IBM KADER UKS (UNIT KESEHATAN SEKOLAH) MELALUI PELATIHAN DOKTER KECIL DI SDN TINOM GODEAN SIDOARUM SLEMAN - Fitriahadi, Enny (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Abstract: Background: The results of observation on Tuesday, August 8, 2017 at SD Negeri Tinom, by conducting interviews obtained UKS space already exist but not yet optimally utilized, has been established UKS teacher builder but not yet understand the duties and functions of teachers of UKS builders, in schools as well there has never been coaching UKS by puskesmas and health counseling then proposer asked 5 students about UKS, many students do not understand about the function of UKS and have never received training about small doctor.Target and Output: The establishment of small doctors and UKS activities runs optimally and the publication of articles in community service journals.Methods of implementation: Socialization of School Health Effort (UKS) at Elementary School level, training of small doctor cadres at primary school level, establishment of small doctor cadres and administration of recording and reporting of UKS activities.Conclusion: With the education and empowerment of teachers and students at SDN Tinom Godean on the empowerment of UKS through the training of small doctors as an effort to improve students' health. The outcomes are strong determination and awareness of students and teachers to jointly improve the health of children through small doctor training activities and optimization of UKS activities accompanied by UKS teachers.?